An In-Depth Study Of Project Management In Construction Services Engineering: Focus On Hong Kong - Ran, Ren; Al-Odaini, Aiman (Cuestiones de Fisioterapia, 2023)
With a specific focus on the impact of green building standards, this study presents an extensive assessment of project management in hong kong's construction services engineering industry. Distinctive issues with efficiency, sustainability, and quality arise in hong kong's construction sector due to the city's increased population density, rigid rules, and significant dependence on massive infrastructure projects. The purpose of this study was to specify how construction services engineering outputs are affected by project management methods especially by the incorporation of green building standards like beam plus. The study was performed using a quantitative approach and responses were gathered from different professional groups using stratified sampling. Using spss version 25, the researcher analysed 449 authentic responses. To ensure reliability and detect significant associations, the researcher used descriptive statistics, anova and factor analysis. The results showed that green building requirements were significantly associated with more profitable construction services engineering. Additionally, the implementation of green standards had the impact of enhancing collaboration across interdisciplinary teams which in turn led to a decrease in disputes and an improvement in adherence with rules. In spite of these benefits, there were a number of challenges that were noted including high costs, the demand for professional training, and resistance to organisational change. The majority of respondents believe that green building standards provide the groundwork for innovation, sustainability and the accomplishment of success in projects over the course of a longer period of time. Findings from the research highlight the significance of strong institutional backing, ongoing professional development and superior project management to accomplish complete integration of green standards within the construction services engineering industry of hong kong.